Improving Pedagogical Competence for Christian Educator - Keysa Febianola (Program Studi Pendidikan Agama Kristen, Fakultas Ilmu Pendidikan Kristen IAKN Tarutung, 2022)
This study aims to describe the importance of improving pedagogical competence for Christian educator. The study used quantitative methods. Samples were taken randomly and processed using SPSS 25.0. Data obtained by using questionnaires was then tabulated and tested with simple linear regression. The results of the study can be concluded that pedagogical competence of teachers of Christian education can be improved through understanding of their calling as teachers. This can be seen from the results of the R-Square determination coefficient which shows a figure of 0.523, which means that the influence of independent variables (X) on dependent variable changes (Y) is 52.3% while the remaining 47.7% is influenced by other variables